INTEGRASI PENANGANAN TINDAK KORUPSI DITINGKAT ASN (APARATUR SIPIL NEGARA) DILINGKUNGAN PEMERINTAH KABUPATEN BONE BOLANGO - Anita Olii (LPPM UNiversitas Bina Mandiri Gorontalo, 2026)
Analysis of the implementation of anti-corruption policies within the Bone Bolango Regency government, especially at the Bappeda Litbang and Inspectorate, based on the results of the research shows that there are already anti-corruption policies such as those related to the ASN code of ethics, integrity pacts and action plans but their implementation is not optimal, this can be seen from the low awareness of ASN of the risks of corruption, as well as the occurrence of ethical violations and corrupt acts, perhaps one of the main obstacles includes a permissive bureaucratic culture. In this case, the Inspectorate as supervision has carried out its system through internal audits, but is still constrained by limited human resources, budget and follow-up on audit results. Collaborative efforts with external institutions have also been carried out, such as with BPK and KPK, in the form of coordination and anti-corruption education. From the results of the research, it can be concluded that it is necessary to strengthen the implementation of anti-corruption policies by conducting regular socialization, training/guidance, increasing human resources in this case, especially certified auditors, and implementing a secure and integrated reporting system. The application of sanctions that must run effectively and a culture of integrity that can start from the leadership are key in preventing acts of corruption. Strengthening collaboration between oversight institutions and periodic evaluation of policy implementation also need to be considered to support the development of clean and integrated governance. Keywords : anti-corruption, ASN, Bone Bolago, integrity, supervision, Inspectorate